Optimalisasi Kinerja Sekolah Melalui Penerapan Manajemen Berbasis Sekolah - Letari, Usnul; Ramli, Rosmiati; Irma, Irma; Tajuddin, Tajuddin; Taufik, Taufik; Saleh, Abd. Rahman (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sulawesi Tenggara, 2025)
The implementation of School-Based Management (SBM) is an approach that provides more autonomy to schools in managing resources and making policies tailored to the needs and potentials of the school. The main goal of SBM is to enhance educational quality through the active participation of all stakeholders, including school principals, teachers, students, parents, and the community. This study aims to analyze the optimization of school performance through the implementation of SBM based on existing literature. The findings show that SBM can improve learning effectiveness, teaching quality, and the relationship between schools and the community. However, challenges such as the lack of training for educators, limited resources, and resistance to change remain major obstacles in the implementation of SBM. This study also emphasizes the crucial role of school leadership in managing this process to achieve SBM’s objectives optimally